Investigation into the Antibacterial Activity of Metal Complexes Derived from Substituted Chromone in Comparison with Tetracycline, and Cephradine as Standard Drugs against Escherichia coli and Staphylococcus aureus - Hoda Pasdar; Naser Foroughifar; Bahare Hedayati Saghavaz (Pasteur Institute of Iran, 2015)
Introduction: The chemistry of metal complexes derived from heterocyclic compounds has attracted considerable interest due to the broad range of pharmacological activities of such compounds. The important pathogens such as Escherichia coli, and Staphylococcus aureus are wildly caused many diseases. So antibacterial activity of Zn (Ⅱ), Ni (Ⅱ), Co (Ⅱ) and Cu (Ⅱ) chromone complexes against two kinds of bacteria was established. Methods: In this study, antibacterial activity of metal complexes derived from 2-amino-7, 7-dimethyl-5-oxo-4-methylbenzen5, 6, 7, 8-tetra hydro-4H-chromone-3-carbonitrile were studied.  The metal complexes were characterized by FTIR, UV-Vis and Mass spectroscopy. Antibacterial effect of these compounds was evaluated by disc diffusion and micro broth dilution methods. Results: The results obtained in this study demonstrate that all the complexes have square planner geometry with the stoichiometry 1:2 (Metal: Ligand). Among the tested compounds the most effective compound was the Cu complex with MIC value of 62.5 mg/mL against E. coli and 125 mg/mL against S. aureus. Conclusion: The results of these studies show that metal the metal complexes had higher antibacterial activity against species when compared to parent ligand.